Dye-synthesized N, S co-doped carbon via plasma engineering as metal-free oxygen reduction reaction electrocatalysts. (9th November 2021) - Son, Hyunjee; Kim, Seonghee; Lee, Jin Hong; Li, Oi Lun
Abstract: Emerging metal-free heterogeneous element-doped carbon-based catalysts have shown advantages of high catalytic efficiency and low cost, and are regarded as a promising alternative to metal catalysts in alkaline-based fuel cells and metal–air batteries. Methylene blue, commonly used to stain specimens, has been causing serious marine pollution and should be considered for eco-friendly recycling. In this study, methylene blue was chosen as an additive and precursor for N- and S-doped carbon nanoparticles and was dissolved in quinoline (C9 H7 N) to synthesize N, S co-doped carbon electrocatalysts via plasma engineering. Based on the electrochemical analysis conducted using a rotating ring disk electrode system, compared to the carbon catalyst synthesized from pure quinoline, the oxygen reduction reaction (ORR) performance was enhanced by increasing the amount of methylene blue ( E onset = 0.78 V (vs RHE) at 100% quinoline, 0.79 V (vs RHE) at 1 mM MBQ-G, 0.84 V (vs RHE) at 2 mM MBQ-G, and 0.86 V (vs RHE) at 3 mM MBQ-G). From the electrochemical results, the onset potential ( E onset ), half-wave potential ( E 1/2 ), and Tafel slope of 3 mM MBQ-G showed the best performance among all the carbon-based catalysts. In addition, the durability properties of 3 mM methylene blue (declined 30 mV after 6000 cycles) is superior to that of the benchmark ORR catalysts of 20 wt.% Pt/C (declined 60 mV after 6000 cycles). Through this study, we have successfully shown the possibility to effectively recycle methylene blue, which often causes marine and water pollution in the dyeing industry, as a useful precursor in carbon-based catalytic materials.